STRATEGI PENGELOLAAN EKOSISTEM TERUMBU KARANG DI WILAYAH PESISIR KABUPATEN LUWU TIMUR - Ayyub, Fachrie Rezka; Rauf, Abdul; Asni, Andi (Universitas Negeri Makassar, 2018)
This study aims to determine the extent of damage to coral reef ecosystems in East Luwu regency, determine the causes of coral reef ecosystem damage and formulate the right strategy plan to preserve the ecosystem of coral reefs. The results showed that the condition of coral cover in medium category (average percentage of live hard coral 32,7%).Damage to coral reef ecosystem caused by destructive fishing fish bombing and anesthesia activity (51,68%), sedimentation factor and eutrophication (25,97%), fishing gear, anchor and ship grouding (20,57%), and predation factor (1.79%).The priority of coral reef management plan are: (1) Rehabilitation of coral reef habitat and endangered species protection; (2) Rehabilitation of forest area in the upper river area; (3) Modernization of fishing and utilization of appropriate technology; (4) Establishment of a network of Conservation Areas for the protection of coral reef ecosystems; (5) Integration of zoning plan of coastal and marine areas with Provincial Government; (6) Development of reception facilities and integrated wastewater treatment plant in coastal areas; (7) Optimization of infrastructural facilities and infrastructure for coral reef ecosystem supervision; (8) Empowerment of community watchdog groups to support the intensification of supervision; (9) Increasing the human resources of the apparatus through technical training on the supervision and management of coral reef ecosystem; and (10) Development of tourism and environmental services to support economic improvement of the community.